Security access permission authentication simulation of multi-source network big data based on blockchain - Bin LI; Hui HE; Zhongying ZHAO; Jingwei GUO (Dianxin kexue)
The frequent interaction and storage of big data in multi-source networks have broken traditional data silos, enabling cross regional and cross organizational data access, posing significant challenges to data security and privacy protection.As one of the technologies to protect data and resource security, access authentication faces enormous communication loads while obtaining trust from all data nodes, which can cause data loss and damage.Therefore, a blockchain based research method for multi-source network big data security access permission authentication was proposed.The transformation status of data in network transmission using similarity relationships was measured, and the probability of multi-source network data access based on the similarity matrix was calculated.The data security access contracts were established through blockchain technology, calibrating data access attributes and transaction ciphertexts, and compressing data within corresponding attributes.The access reliability based on the purpose of the access was analyzed, reliability was used as the standard to correspond to the security level, rules under different levels of reliability were accessed, specific permissions were authenticated for data security access, and implementation methods were designed.The experimental results show that using different data attribute contents as testing conditions, encrypting and decrypting data in both conventional and attack modes, the new method can achieve fast authentication response and secure access to network data.